INOVASI PENGEMBANGAN KAWASAN WISATA CAGAR BUDAYA (TONGKONAN TUA SILLANAN DAN BUNTU SURIAK) - Tadius, Tadius; Kristanto, Kristanto; Jery, Jery (LPPM Universitas Bina Bangsa, 2025)
Innovation in Developing Cultural Heritage Tourism Areas at Tongkonan Tua Sillanan and Buntu Suriak aims to explore, develop, and promote Lembang Sillanan tourism to establish it as a tourist village. The innovation focuses on leveraging local cultural potential and the natural scenic beauty, particularly in the Sillanan area. This research explores various strategies to enhance the appeal of Tongkonan Tua Sillanan and Buntu Suriak, empower the local community, and utilize information technology. The method employed in this community engagement activity is a qualitative descriptive approach. Through qualitative methods and participatory analysis, the study identifies sustainable development opportunities for Lembang Sillanan’s tourist attractions, which could increase visitor numbers, provide economic benefits for the community, and allow people to enjoy the natural beauty of Lembang Sillanan.The findings indicate that the introduction of digital tourist guides, the provision of gazebo locations for relaxation, and the promotion of local culture can serve as key pillars in transforming Lembang Sillanan into an attractive tourist destination. The use of social media and storytelling-based promotion, as well as digital technology, is proposed to enhance visitor engagement through virtual tours and app-based experiences, such as vlogs uploaded to social media platforms